Auditing theory for students & practice guide for auditors - Racaza, Concepcion Rasalan; Evangelista, Rosalinda Datu (Manila, Philippines : Conanan Educational Supply, 2011)
This edition maintains the traditional features of the earlier editions: concepts balanced with practical applications, focus notes and summary of key points.
Unit I : Introductory matters -- Unit II : Planning and understanding internal control -- Unit III : Conducting audit -- Unit IV : Audit conclusions and reporting -- List of Figures -- Appendix.
Keywords: AUDITING